Evaluación del nivel de severidad de las enfermedades foliares más comunes en cinco híbridos de maíz (Zea mays L.) en la zona de Mocache - Carpio Salazar, Jasmany Catalino (2023)
The objective of this investigation was to evaluate the level of severity of foliar diseases in five maize hybrids in the Mocache area. The trial was carried out at the "La María" Campus of the Quevedo State Technical University, located at km 7.5 of the Quevedo - El Empalme road, Los Ríos province. Five maize hybrids were evaluated: T1: ADV-9789; T2: ADV-9139; T3: Splendor; T4: Emblem and T5: Triumph, under a randomized complete block design in four repetitions. The results obtained showed that the Triunfo hybrid showed a lower incidence of the evaluated foliar diseases, with values that ranged between 15.25 (Puccinia sorghi) and 17.00 % (Spiroplasma kunkelii and Physoderma maydis), while their severity fluctuated from 7.55 (Puccinia sorghi) to 8.16% (Spiroplasma kunkelii). Advanta 9789 was the hybrid that stood out among the planting materials evaluated, since it produced a higher level of yield (8213.64 kg), as a result of the production of longer ears, which in turn contributed to obtaining a greater net weight. of grain for each ear harvested. Finally, the profitability of the hybrids ranged between 28.26 and 50.95%, being the most profitable ADV-9789, and although the Triunfo hybrid had a lower variable cost than the other hybrids, its performance is the lowest, net income and profitability are significantly lower than those of the other hybrids. Keywords: plant health, hybrids, corn, yield, profitability